On p-Cyclic Orbital M-K Contractions in a Partial Metric Space - Tharmalingam Gunasekar; Saravanan Karpagam; Boyan Zlatanov (Mathematics, 2018)
A cyclic map with a contractive type of condition called p-cyclic orbital M-Kcontraction is introduced in a partial metric space. Sufficient conditions for the existence and uniqueness of fixed points and the best proximity points for these maps in complete partial metric spaces are obtained. Furthermore, a necessary and sufficient condition for the completeness of partial metric spaces is given. The results are illustrated with an example.